Assessing the Interactions between Macroeconomic Indicators and the Dhaka Stock Exchange Performance - Sarmin Rahman; Farhana Akter (International Journal of Financial, Accounting, and Management, 2026)
Purpose: This study aims to examine the association between the Dhaka stock exchange and financial indicators in Bangladesh and provide insights for policymakers and economists to make informed decisions regarding the nation's economic advancement in the short and long terms. Research Methodology: This study employs a time-series econometric data analysis approach from July 2009 to December 2022 in Bangladesh, utilizing various statistical approaches, including long-run and short-run dynamics (VECM), and short-run causal relationships (Granger causality relationship test) among variables using EViews13. Results: The study found a robust inverse association between stock market capitalization and interest rates, as well as the inflation rate. and a negligible inverse relationship with the exchange rate. The Granger Causal Test shows a short-term unidirectional causal relationship between the interest rate and market capitalization, as well as between the market capitalization and conversion rate. Conclusions: This study contributes to the existing literature by providing a comprehensive analysis of the Dhaka Stock Exchange in relation to key financial indicators over an extended period (2009–2022), which has not been explored extensively. Limitations: Our limited dataset may affect the external applicability of the findings to other regions. In addition, our time-series approach may not capture structural breaks during the period of analysis. Contributions: This article presents an analytical study that employs contemporary time-series data to assist economists and finance experts in making informed investment decisions regarding the stock market in the upcoming period.